Supercritical carbon dioxide immobilization of glucose oxidase on conducting polymers towards biosensor production - Talay, Defne Kayrak. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
In this work, glucose oxidase (GOX) is immobilized on conducting polymer matrices (polypyrrole film, PPY; polyurethane/polpyrrole composite foam and film, PU/PPY) via Supercritical Fluid Immobilization (SFI) for further use in the preparation of biosensors. Initially, the effects of supercritical carbon dioxide (scCO2) pressure (80-150 bar, 40 oC) and temperature (30-60 oC) on free-enzyme buffer-solution activity are investigated for 24 h scCO2 exposure time. Results show that enzymatic activity of GOX after exposure to scCO2 is retained. The enzymatic activity of GOX-buffer solution does not show a decrease between 30-50 oC, whereas 30 per cent and 94 per cent activity losses are noticed at 55 and 60 oC temperatures. In order to provide an insight into the relation between the scCO2 and the GOX-buffer solution, the GOX-buffer solutions were subjected to scCO2 and the protein amounts of the GOX-buffer solutions before and after scCO2 exposure were determined at 80, 100 and 150 bar and 30, 40 and 50 oC for an exposure time of 24 h. Results showed that the protein amount in GOX-buffer solution decreased in all cases after exposure to scCO2. The decreases in GOX amount are 18, 14.3 and 49.5 per cent compared to the original value at 100 bar, 30, 40 and 50 oC, respectively. The GOX immobilized polymer matrices are analyzed via Environmental Scanning Electron Microscopy (ESEM) and enzymatic activity methods. To determine the immobilization medium to be used on PPY films, four different immobilization mediums were tried. These were: Dry GOX and dry PPY (Dry); dry GOX and dry PPY with water vapor (Semi-Dry); GOX and PPY in water (Wet); GOX and PPY in buffer (Wet-b). In “Dry” and “Semi-Dry” procedures (up to 150 bar, 40 oC and 72 h), the PPY films showed no noticeable activity, whereas films processed in “Wet” and “Wet-b” methods showed enzymatic activity. In “Wet” method (150 bar and 40 oC), as the immobilization time increased (5-72 h) the activity also increased. The maximum activity is observed for GOX immobilized PPY film in the “Wetb” medium. Thus, during GOX immobilization of PU/PPY, buffer solution is used as the immobilization medium. The effects of immobilization time (4, 24, 72 h), immobilization solution concentration (6.25, 0.625 and 0.0625 mg/ml), washing procedures of samples prior to and after the immobilization process, temperature (30, 40 and 50 oC) and pressure (80, 100, and 150 bar) on the activity of PU/PPY samples are determined. The immobilized GOX amounts on the polymer samples are also measured. Decreasing the initial concentration of GOX solution two orders of magnitude enhances the specific activity of the immobilized on PU/PPY composite GOX by 25 fold. As the washing steps get longer, the activity of the sample increases. Washing the sample in scCO2 before immobilization also increases the activity compared to non-CO2 washing procedure. Increasing immobilization time from 4 to 24 h leads to the activity enhancement by 71.8 per cent, and an increase from 24 h to 72 h caused 16.4 per cent decrease in activity. The immobilized amount of GOX on PU/PPY composite increased as the temperature increased at all pressures and decreased as the pressure increased at all temperatures. The specific activity value (U/mg) increased as the pressure increased from 80 to 100 bar, however further increase to 150 bar did not cause any increase in specific activity. At constant pressure, as the temperature increased, the specific activity decreased. The highest activity and highest specific activity for the samples processed at supercritical conditions were obtained at 100 bar, 30 oC as 0.040 U/cm2 and 4.9 U/mg, respectively. When immobilization was performed via SFI, the activity values were doubled compared to the immobilization at atmospheric conditions. This might mean using less enzyme to get same activity, thus cheaper biosensor of equal performance.
Keywords: Biosensors.; Supercritical fluid extraction.; Carbon dioxide.